2019
DOI: 10.3390/bioengineering6040107
|View full text |Cite
|
Sign up to set email alerts
|

Structures and Applications of Thermoresponsive Hydrogels and Nanocomposite-Hydrogels Based on Copolymers with Poly (Ethylene Glycol) and Poly (Lactide-Co-Glycolide) Blocks

Abstract: Thermoresponsive hydrogels showing biocompatibility and degradability have been under intense investigation for biomedical applications, especially hydrogels composed of hydrophilic poly(ethylene glycol) (PEG) and hydrophobic poly(lactic acid-co-glycolic acid) (PLGA) as first-line materials. Even though various aspects such as gelation behavior, degradation behavior, drug-release behavior, and composition effect have been studied for 20 years since the first report of these hydrogels, there are still many outp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 68 publications
0
24
0
Order By: Relevance
“…However, temperature enhances the hydrophobic effect driving a greater fraction of micelles to form, potentially altering micelle shape, and enhancing inter‐micelle interactions which in turn induces gelation. [ 15 ] Poloxamers, in particular, have been widely studied and are appealing due to their history of use in human medicine. [ 16,17 ] However, there are several limitations of these materials, including a high dependence of T gel on polymer concentration leading to a reverse gel–sol transition upon dilution, [ 18 ] weak gel strengths for some applications such as mucosal drug delivery and 3D printing, [ 17,19 ] and low long‐term cell viability in their presence for tissue engineering and cell culture purposes.…”
Section: Introductionmentioning
confidence: 99%
“…However, temperature enhances the hydrophobic effect driving a greater fraction of micelles to form, potentially altering micelle shape, and enhancing inter‐micelle interactions which in turn induces gelation. [ 15 ] Poloxamers, in particular, have been widely studied and are appealing due to their history of use in human medicine. [ 16,17 ] However, there are several limitations of these materials, including a high dependence of T gel on polymer concentration leading to a reverse gel–sol transition upon dilution, [ 18 ] weak gel strengths for some applications such as mucosal drug delivery and 3D printing, [ 17,19 ] and low long‐term cell viability in their presence for tissue engineering and cell culture purposes.…”
Section: Introductionmentioning
confidence: 99%
“…When the solution temperature is increased, polymer-water hydrogen bonding becomes weaker, while the hydrophobic interactions between micelles become stronger; this results in the formation of a networks or aggregates of micelles. [170] In one study, Singh et al reported thermo-and pH-sensitive injectable hydrogels composed of poly( -caprolactone lactide) (PCLA)-PEG-PCLA-PAEU multiblock copolymers. The nega-tively charged human growth hormone (hGH) was interacted with the positively charged surface of 2D-layered double hydroxide NPs (LDH).…”
Section: Temperature-responsive Injectable Hydrogels For Controlled Amentioning
confidence: 99%
“…The gel strength depends on the number, size, and geometry of hydrophobic domains. The properties can also be modified by surfactant or salt addition [ 34 , 35 ]. The ease of recreating hydrophobic interactions makes these gels exhibit excellent self-healing properties.…”
Section: Interactions In Supramolecular Hydrogelsmentioning
confidence: 99%
“…The ease of recreating hydrophobic interactions makes these gels exhibit excellent self-healing properties. The damaged hydrogel usually can be repaired at room temperature, regaining its mechanical properties [ 1 , 11 , 26 , 35 , 36 , 37 , 38 ]. The hydrogels which are formed by hydrophobic interactions often exhibit interesting negatively thermo-responsive behavior (the temperature increase causes the gelation process).…”
Section: Interactions In Supramolecular Hydrogelsmentioning
confidence: 99%